Homeobox C10 inhibits the osteogenic differentiation potential of mesenchymal stem cells. (4th May 2018) - Li, Guoqing; Han, Nannan; Yang, Haoqing; Wang, Liping; Lin, Xiao; Diao, Shu; Du, Juan; Dong, Rui; Wang, Songlin; Fan, Zhipeng
ABSTRACT: Purpose: Mesenchymal stem cells (MSCs) are a reliable cell source for tissue regeneration. However, the molecular mechanisms underlying the directed differentiation of MSCs remain unclear which impedes potential clinical applications. Recent studies have discovered that Homeobox (HOX) genes are involved in the differentiation regulation of MSCs and bone formation. In this study, we investigate the HOXC10 function in the osteogenic differentiation potential of MSCs. Materials and Methods: Stem cells from apical papilla (SCAPs) and adipose-derived stem cells (ADSCs) were used in this study. Alkaline phosphatase (ALP) activity assays, ALP staining, Alizarin red staining, quantitative calcium analysis, osteogenesis-associated gene expression, and in vivo transplantation experiments were used to study osteogenic differentiation potential. Results: Our results showed that overexpression of HOXC10 in SCAPs inhibited ALP activity and mineralization in vitro and decreased the mRNA expression of collagen alpha-1 (I) chain, bone sialoprotein, osteocalcin, and a key transcription factor, runt-related transcription factor 2, in SCAPs. Depletion of HOXC10 promoted osteogenic differentiation in SCAPs in vitro . In addition, in vivo transplantation experiments in nude mice confirmed that SCAPs osteogenesis was triggered when HOXC10 was downregulated. Furthermore, depletion of HOXC10 also enhanced osteogenic differentiation in ADSCs. Conclusions: Taken together, these results indicated that HOXC10 decreased the MSC osteogenic differentiation potential. Thus, inhibition of HOXC10 in MSCs might have the potential to improve tissue regeneration and provide insight into the mechanism underlying the directed differentiation of MSCs.